2019
DOI: 10.1128/iai.00742-18
|View full text |Cite
|
Sign up to set email alerts
|

The Pneumococcal Surface Proteins PspA and PspC Sequester Host C4-Binding Protein To Inactivate Complement C4b on the Bacterial Surface

Abstract: Complement is a critical component of antimicrobial immunity. Various complement regulatory proteins prevent host cells from being attacked. Many pathogens have acquired the ability to sequester complement regulators from host plasma to evade complement attack. We describe here how Streptococcus pneumoniae adopts a strategy to prevent the formation of the C3 convertase C4bC2a by the rapid conversion of surface bound C4b and iC4b into C4dg, which remains bound to the bacterial surface but no longer forms a conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
0
25
0
Order By: Relevance
“…Cutoffs of absolute gene expression (fold-change: >1.2) and a FDR ( q -value < 0.05) were applied to select DEGs between ACE2 -expressing ( n = 607) and ACE2 -absent ( n = 26,628) AT2 cells. Among genes upregulated in ACE2 -expressing AT2 cells, we identified genes that are highly pertinent to lung epithelial biology and disease such as HHIP (lung branching and COPD [ 24 , 25 ]), FGG (fibrosis, pneumonia, and inflammation [ 26 , 27 ]), and C4BPA (complement system, pneumonia, and infection [ 28 , 29 ]) ( Figure 3 A,B). In addition, we found that ACE2 -expressing AT2 cells exhibited significantly a higher expression of scavengers such as CD36 [ 30 ], as well as DMBT1 , a pattern recognition receptor that plays crucial roles in host defense against bacterial and viral pathogens, including influenza A and human immune deficiency virus 1 (HIV-1) [ 31 ] ( Figure 3 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutoffs of absolute gene expression (fold-change: >1.2) and a FDR ( q -value < 0.05) were applied to select DEGs between ACE2 -expressing ( n = 607) and ACE2 -absent ( n = 26,628) AT2 cells. Among genes upregulated in ACE2 -expressing AT2 cells, we identified genes that are highly pertinent to lung epithelial biology and disease such as HHIP (lung branching and COPD [ 24 , 25 ]), FGG (fibrosis, pneumonia, and inflammation [ 26 , 27 ]), and C4BPA (complement system, pneumonia, and infection [ 28 , 29 ]) ( Figure 3 A,B). In addition, we found that ACE2 -expressing AT2 cells exhibited significantly a higher expression of scavengers such as CD36 [ 30 ], as well as DMBT1 , a pattern recognition receptor that plays crucial roles in host defense against bacterial and viral pathogens, including influenza A and human immune deficiency virus 1 (HIV-1) [ 31 ] ( Figure 3 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…FGG coding for fibrinogen-gamma was shown to be induced by proinflammatory cytokines [ 27 ] and to be elevated in lung pneumonia and infection [ 26 ]. C4BPA , coding for C4BP and part of the complement system, was found to recognize and bind pneumonia-causing streptococci in the lung epithelium [ 28 , 29 ]. It is noteworthy that many patients with COVID-19 (e.g., those with severe disease) commonly display the same pathological phenotypes, namely lung inflammation, fibrosis, and pneumonia, linked to those ACE2- co-expressed genes.…”
Section: Discussionmentioning
confidence: 99%
“…Through a linear mixed model GWAS analysis, we have identified genome-wide statistically significant genetic variation differentially abundant in CNS and non-CNS isolates in genes, which encodes a surface-exposed protein (pspC or cbpA) and a hypothetical DnaQ/DinG exonuclease/helicase family gene with unknown function. The PspC protein is a multifunctional choline-binding protein, which binds to human factor H 65 , complement inhibitor C4b 66 and inhibits complement C3 deposition 67 , which promotes immune evasion and virulence 67,68 . Crucially, experimental studies have shown that interactions between PspC and the C-terminus of the lamininintegrin receptor, initiates contact with the vascular endothelium of the blood-brain barrier, which improves pneumococcal tropism to the CNS 69 , a mechanism also utilised by other respiratory bacterial pathogens 69 , neurotropic viruses [70][71][72][73] and prions 74 .…”
Section: Discussionmentioning
confidence: 99%
“…C4bp binding to PspC, PspA, LytA, and PepO (Pneumococcal endopeptidase O) has been demonstrated. Pneumococcal surface-bound C4bp retains its cofactor activity for factor I-mediated cleavage of C4b [72,73]. The role of LytA in complement evasion has only been recently elucidated.…”
Section: Acquisition Of Soluble Complement Regulatorsmentioning
confidence: 99%